(untitled) (Research, Society and Development, 2021)
Objective: Describe the creation of an application on the Android® operating system that provides information for optimizing the management process of public procurement of medicines. Methods: An exploratory experimental study was carried out, divided into the following steps: review of legislation and literature, development of the prototype through a website and usability assessment through a specific questionnaire developed by the Federal University of Santa Catarina (GQS/UFSC) - questionnaire MATCH. Result: Definition of documents and information to be used in the application, according to the bibliographic research, demonstration of the resources available in the application, and application of the MATcH questionnaire, to validate the prototype’s usability. Conclusion: it was found with this study that Logmed is a useful tool for monitoring the process of managing the acquisition of medicines, aiming to avoid shortages and the consequent damages in care.